ANALISIS PERHITUNGAN LIFTING PLAN PADA PEKERJAAN KONSTRUKSI BREAKWATER TERMINAL LPG JAWA TIMUR - Setiawan, Febri Dwi; Saputra, Pungky Dharma (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2025)
Abstract: This study aims to analyze the lifting plan calculation in offshore pile installation works for breakwater construction at the East Java Refrigerated LPG Terminal Project Phase 2. The research employs a descriptive quantitative approach through direct field observation of lifting activities using a crawler crane operating on a working barge. The analysis includes the calculation of total lifting load, dynamic load correction using the dynamic amplification factor (DAF), effective crane capacity based on the load chart, as well as evaluation of crane utilization and safety factor as indicators of operational safety. The results indicate that the lifting of steel pipe piles from the service barge to the working barge achieved a crane utilization of 65.29% with a safety factor of 1.53, representing a safe and optimal condition. In the pile-to-launch lifting process using a pile gripper, utilization increased to 81.38% with a safety factor of 1.23, indicating a near-critical operational condition. Meanwhile, lifting operations involving the vibro hammer and impact hammer showed utilization levels of 49.25% and 75.18%, respectively, with safety factors above 1.33, indicating safe to highly safe conditions. Overall, the findings demonstrate that lifting plan performance is strongly influenced by equipment configuration, lifting load, and offshore environmental conditions, highlighting the need for comprehensive technical evaluation to ensure operational safety and efficiency. Keywords: Lifting plan, Crawler crane, Dynamic amplification factor, Safety factor ,Offshore construction